Studies on Arylhydrazones Part XV: Reduction of Ethyl 2,3-dioxo-2-o-nitrophenylhydrazono Butyrate - Sahay, Anup (Asian Journal of Chemistry, 2010)
Reduction of ethyl 2,3-dioxo-2-o-nitrophenylhydrazono butyrate wascarried out using various reducing agents such as FeSO4 /NH3, NH4Cl /Zndust, Sn/HCl, Zn/CH3COOH, Zn/HCl, SnCI2/HCI, H2S/alc. NH3 andsodium dithionite. In all the above methods of reduction, the reductionwith Na2S2O4 was proved to be an efficient and excellent method due toeasier process, a much better yield of amino compound in spite of theformation of the sodium salt of o-sulphamic acid to a greater extent.Reduction product (amino compound) was isolated and characterised byphysical and spectral methods. Finally the amino compound was establishedby forming the N-formyl and N-acetyl derivatives from the sodiumsalt of o-sulphamic acid and the various condensation products (anils) withdifferent aldehydes.